Analisis Pengesahan Penyesuaian Batas Antara Flight Information Regional Jakarta Dan Flight Information Regional Singapura Dengan Peraturan Presiden Nomor 109 Tahun 2022 - Prayitno, Budi; Pramono, Agus; Sudarto, Sudarto (LITERATUS, 2024)
The flight information region adjustment agreement between Indonesia and Singapore, as the Realignment Flight Information Region Agreement, has been ratified by Presidential Regulation Number 109 of 2022 concerning Ratification of the Agreement between the Government of the Republic of Indonesia and the Government of the Republic of Singapore concerning the Adjustment of Boundaries between the Jakarta Flight Information Region and the Singapore Flight Information Region on September 5, 2022. The problem to be discussed is How are the regulations for ratification of boundary adjustments between Jakarta flight information regional and Singapore flight information regional based on laws and regulations in Indonesia? and What are the implications of ratifying the adjustment of the boundaries between Jakarta's regional flight information and Singapore's regional flight information with presidential regulation number 109 of 2022?. With the normative legal research method (normative legal research). The regulation of ratifying the adjustment of the boundaries between Jakarta's regional flight information and Singapore's regional flight information is regulated by Law Number 1 of 2009 concerning Aviation and its implementing regulations. This law also refers to the regulations of the International Civil Aviation Organization (ICAO), which is a global reference in the management of airspace and FIR as well as the Indonesia-Singapore Flight Information Region (FIR) Adjustment Agreement 2022. The implications of ratifying the adjustment of the boundaries between Jakarta's regional flight information and Singapore's regional flight information with presidential regulation number 109 of 2022 occur in the Implications in the political field, Implications in the Economic field and Implications in the field of national defense and security. The regulation of ratifying the adjustment of the boundaries between Jakarta's regional flight information and Singapore's regional flight information Indonesia must strengthen and maintain the FIR areas on maps A and B so that they are not managed again by Singapore. The implication of ratifying the adjustment of the boundaries between Jakarta's regional flight information and Singapore's regional flight information is that Indonesia must think about immediately regulating a Single Air Traffic Provider where all Indonesian airspace is regulated in one FIR (Flight Information Region). Keywords: presidential regulation, FIR, boundary adjustment